Celiac crisis as the life-threatening onset of celiac disease in children: a case report - Mauro, Angela; Casini, Francesca; Talenti, Antonella; Di Mari, Clelia; Benincaso, Anna Rita; Di Nardo, Giovanni; Bernardo, Luca (Frontiers in Pediatrics, 2023)
Celiac disease (CD) is an immune mediated enteropathy, caused by permanent sensitivity to gluten in genetically susceptible individuals. In rare cases, CD may occur with a severe potential life-threatening manifestation, known as celiac crisis (CC). This may be a consequence of a delayed diagnosis and expose patients to possible fatal complications. We report the case of a 22-month-old child, admitted to our hospital for a CC characterised by weight loss, vomit and diarrhoea associated with a malnutrition state. Early identification of symptoms of CC is essential to provide a prompt diagnosis and management.